2020
DOI: 10.1017/s0033291720001634
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of neurocognitive deficits in unaffected relatives of obsessive-compulsive disorder (OCD): comparison with healthy controls and patients with OCD

Abstract: BackgroundObsessive-compulsive disorder (OCD) has been associated with cognitive deficits, particularly with executive functions. These findings support fronto-striatal dysfunction in OCD. However, it is not certain whether these findings are trait features of OCD. In recent years, a number of studies have investigated cognitive functions in unaffected relatives of OCD (OCDrel) but the findings of these studies are contradictory.MethodsA systematic review in Pubmed and Scopus databases was performed until 18 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 63 publications
1
28
0
1
Order By: Relevance
“…This result means that the aberrant rsFC between the cerebellum and DMN is not associated directly with the obsessive-compulsive symptoms. DMN relates to response inhibition (66,67), planning (68), and decision-making (69), which are trait markers for OCD (70). Our results, therefore, might show that this aberrant rsFC is not a state but a trait of OCD patients.…”
Section: Discussionmentioning
confidence: 72%
“…This result means that the aberrant rsFC between the cerebellum and DMN is not associated directly with the obsessive-compulsive symptoms. DMN relates to response inhibition (66,67), planning (68), and decision-making (69), which are trait markers for OCD (70). Our results, therefore, might show that this aberrant rsFC is not a state but a trait of OCD patients.…”
Section: Discussionmentioning
confidence: 72%
“…A number of studies have identified shared features between OCD and their UFDR. For instance, a meta‐analysis of OCD suggested that abnormalities in inhibition, planning/problem solving, and reward‐based decision‐making are shared features of OCD and their UFDR and might be trait markers related to vulnerability for developing OCD (Bora, 2020 ). Dong and colleagues found that the same changes in effective connectivity were present in both OCD patients and their unaffected first‐degree relatives (Dong et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neurocognition represents one of the key mechanisms by which changes in brain structure and function ultimately give rise to clinical signs and symptoms. Lying closer to the putative biological substrate and being measurable on objective tests, neurocognitive markers may be more reliable, consistent and enduring than the variably expressed symptoms of a disorder [118][119][120] . Neurocognitive testing in patients with OCD and related disorders, for example, has been used to characterize abnormalities of fronto-striatal circuitry compared to controls 121 , as well as to identify putative subtypes with different brain structure, function and connectedness 122 .…”
Section: Neurocognitionmentioning
confidence: 99%